Effect of Cranberry Extract on the Frequency of Bacteriuria in Dogs with Acute Thoracolumbar Disk Herniation: A Randomized Controlled Clinical Trial. (3rd December 2016) - Olby, N.J.; Vaden, S.L.; Williams, K.; Griffith, E.H.; Harris, T.; Mariani, C.L.; Muñana, K.R.; Early, P.J.; Platt, S.R.; Boozer, L.; Giovanella, C.; Longshore, R.
Abstract : Background: Dogs with spinal cord injury are at increased risk of developing bacteriuria due to increased residual urine volume. Cranberry extract inhibits binding of E. coli to uroepithelial cells, potentially reducing risk of bacteriuria. Hypothesis: Cranberry extract reduces risk of bacteriuria in dogs after acute TL‐IVDH. Animals: Client‐owned dogs with acute onset TL‐IVDH causing nonambulatory status. Methods: Randomized, placebo‐controlled, blinded, prospective clinical trial. Dogs with acute TL‐IVDH were recruited 48 hours postoperatively and randomized to receive cranberry extract or placebo in a masked fashion. Urine cultures and neurological examinations were performed 2, 4, and 6 weeks postoperatively. The number of dogs with bacteriuria (all bacterial species) and bacteriuria ( E. coli) were primary and secondary outcome measures and were evaluated using chi‐squared test. Urine antiadhesion activity (AAA) was measured in a subset (N = 47) and examined in a secondary analysis evaluating additional risk factors for bacteriuria. Results: Bacteriuria was detected 17 times in 94 dogs (6 placebo, 11 cranberry, P = .12). There were 7 E. coli . positive cultures (1 placebo, 6 cranberry, P = .09). Dogs in both groups had positive urine AAA (14/21: placebo, 16/26: cranberry), and dogs with urine AAA had significantly fewer E. coli positive cultures (n = 1) than dogs without it (n = 4) ( P = .047). Conclusions and Clinical Importance: This clinical trial did not show a benefit of oral cranberry extract but had low power. Cranberry extract supplementation did not impact urine AAA, but a possible association between urine AAA and lower risk of E. coli bacteriuria was identified. Other doses could be investigated.